The Role Of Social Media Marketing Towards Customer Repurchase Intention For Fashion Apparel With Brand Image As Mediating Variable (A Study In Levi Strauss & Co.) - Marphy, Kana Octafikri (Jurnal Ilmiah Mahasiswa FEB, 2021)
The use of social media in this globalization era is increasing rapidly. Social media is not only used as a communication tool between the user, but also it becomes a platform to purchase, especially for the Gen Z, who tends to shop online. Therefore, many companies use social media marketing to promote their brand and sell their products, including Levi’s. This study aimed to investigate the effect of social media marketing (X) towards repurchase intention (Y) through the brand image (Z) of Levi’s. This study used a quantitative method to analyze the effect between independent, dependent, and mediating variables. The samples were taken from purposive sampling, consisting of 150 Gen Z who live in Malang, have followed or opened Levi’s social media and ever purchased Levi Strauss & Co. Statistical software Smart-PLS was used to analyze the data. The result of this research indicated that social media marketing and brand image positively influence repurchase intention. The other findings showed that brand image has no significant influence in bridging social media marketing on repurchase intention.Keywords: Social Media Marketing, Brand Image, Repurchase Intention